The Role of Kiai Amin in Tanjungrejo Village (Development of Islamic Education Values and Morality) - Thabi’in Ma’ruf (Rayah Al-Islam, 2021)
Kiai's role has a role that can understand the teachings of Islam towards the community both who are still lay and already know Islam. Kiai is the center of the outpouring or solution of the problems faced by the local community. The result of Kiai's role in developing Islamic education in Balekambang, Tanjungrejo Village, Wirosari District, Grobogan Regency is kiai has improved and changed slowly the customs in the village, even making new customs such as tahlilan and yasin activities, sholawatan, manaqiban, and there are private schools such as TPQ, and Madratsah Diniyah that exist from grades 1-6 and at graduation along with Akhirussanah.